Master Regulators of Signaling Pathways: An Application to the Analysis of Gene Regulation in Breast Cancer - Tapia-Carrillo, Diana; Tovar, Hugo; Velazquez-Caldelas, Tadeo Enrique; Hernandez-Lemus, Enrique (Frontiers in Genetics, 2019)
Analysis of gene regulatory networks allows the identification of Master Transcriptional Factors that control specific groups of genes. In this work we inferred a gene regulatory network from a large dataset of breast cancer samples to identify the Master Transcriptional Factors that control the genes within signal transduction pathways. The focus in a particular subset of relevant genes constitutes an extension of the original MARINa analysis. This modified version of MARINa utilizes a restricted molecular signature containing genes from the 25 human pathways in KEGG's signal transduction category. Our breast cancer RNAseq expression data set consists of 881 samples comprising tumors and normal mammary gland tissue. The top 10 Master Transcriptional Factors found to regulate Signal Transduction pathways in breast cancer, we identified are: TSHZ2, HOXA2, MEIS2, HOXA3, HAND2, HOXA5, TBX18, PEG3, GLI2 and CLOCK. The functional enrichment of the regulons of these Master Transcriptional Factors showed an important proportion of processes related to morphogenesis. Our results suggest that, as part of the aberrant regulation of signaling pathways in breast cancer, pathways similar to the regulation of cell differentiation, cardiovascular system development and vasculature development may be dysregulated and co-opted in favor of tumor development through the action of these transcription factors.